KETERBUKAAN EKONOMI DAN PERTUMBUHAN EKONOMI DI LIMA NEGARA ASEAN PERIODE 1996-2017 - Nabila Eka Marza Oktavia; Aris Soelistyo (Jurnal Ilmu Ekonomi JIE, 2020)
This study aims to determine the effect of foreign debt, exports, and inflation on economic growth in the five ASEAN countries in the period 1996-2017. The tool used in this study is multiple linear regression using panel data by testing hypotheses, namely test f, t test, coefficient of determination . The results of this study show together foreign debt, exports, and inflation against economic growth in five ASEAN countries, with a probability value of 0.0000. While individually foreign debt has a negative and significant effect on economic growth with a regression coefficient of -2.599232 and a probability value of 0.0035, exports have a positive and significant effect on economic growth with a regression coefficient of 1.801832 and a probability value of 0.0573, and inflation has a negative and significant effect on economic growth with a regression coefficient of -0.245798 and a probability value of 0.0000.